PERANCANGAN PENJADWALAN PERAWATAN MESIN WRAPPER (PACKING) LINE 13 DENGAN METODE RELIABILITY CENTERED MAINTENANCE II PADA PT XYZ - Erika Rahmi (2022)
PT XYZ is a company that produces food and beverages. From historical data, the wrapper engine has the highest downtime among other machines. This machine is one of the most important machines in determining the quality of the noodle production process. Failures that appear on this machine will have the potential to disrupt the production process so optimal maintenance policy planning is needed. The RCM II method is used to determine the right type of maintenance activity on a piece of equipment through analysis of the impact caused by a failure using FMEA tables and RCM II Decision Diagrams as well as a comparison of reliability after and before preventive maintenance. The results of the calculation of RPN using FMEA obtained 3 engine components that became the focus of research, Namely end sealer components, tubing conveyors, and long sealers. In the study, it was proven by the RCM II formula that the result of the maintenance interval on the end sealer was 68 hours with increasing reliability to 85%, on tubing onveyors it was 72 hours with increased reliability to 92%, on long sealer was 100 hours with increased reliability to 80%. The examination schedule in this study was made for January - December 2022.